Extraction of bioactive compounds from tobacco stems using ultrasound-assisted extraction (UAE) method - Sulihtyorini, Ery; Pranowo, Dodyk; Dewanti, Beauty Suestining Diyah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Tobacco stems (Nicotiana tabacum L.) are abundant agricultural byproducts that are rich in bioactive compounds. Their potential remains underexploited due to limitations in current processing and extraction technologies. This study aimed to identify superior tobacco varieties and optimize Ultrasound-Assisted Extraction (UAE) conditions for total phenolic content (TPC), Total flavonoid content (TFC), and antioxidant activity from tobacco stems. The research was conducted in two sequential stages: (1) Preliminary study for screening of TPC and antioxidant activity of varieties Paiton 4 and Gagang Rejeb Sidi; (2) Experimental set-up using a Randomized Complete Block (RCB) Design was employed, on the selected superior variety, arranged in a factorial with three replications, factors of temperature (i.e., 40, 50, and 60 °C) and extraction time (i.e., 30, 45, and 60 minutes). Preliminary results showed the superiority of Paiton 4, with TPC of 568.09 mg GAE/100 g and the highest antioxidant activity (IC50 of 1286.86 ppm). These results revealed that the best selected treatment achieved at a temperature of 40 °C for 60 minutes, producing the highest TPC (195.64 mg GAE/100 g) and the strongest antioxidant activity (141.87 µg AAE/g). This proved the effectiveness of low-temperature UAE in protecting heat-sensitive compounds, although the highest Total Flavonoid Content was obtained at 45 minutes.